CHALLENGES AND SOLUTIONS OF TVET QUALITY ASSURANCE IN MONGOLIA - Tentere, Grieta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Technical and vocational education and training (TVET) makes a significant contribution to economic competitiveness in a knowledge-based economy. The main challenge for vocational education and training is to meet the changing skill needs in the labour market. In order to balance labour market supply and demand by constantly diversifying TVET customer base, it is necessary to increase the key role played by vocational education and training in economic competitiveness and social inclusion. The considerable economic growth in Mongolia does not have a positive impact on the creation of new jobs and poverty reduction. This implies that the Mongolian education sector was unable to produce required knowledge and skills to be employed. At the system and institutional levels, the management has changed frequently, the policy continuity and consistency are weak. The TVET and curriculum standards are not developed, validated and approved. The multi-faceted, multi-ownership and relatively accessible TVET system became reality in Mongolia. The main factor to increase the economic competitiveness is the quality of in the TVET sector. Thus, the quality assurance is a comprehensive system for evaluating outcomes and achievement of the core objectives of the TVET system, making adjustments, if necessary, and improving a rationale for management decisions.